2008
DOI: 10.1086/591696
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Epidemiology: Hospital Staffing and Health Care–Associated Infections: A Systematic Review of the Literature

Abstract: In the past 10 years, many researchers have examined relationships between hospital staffing and patients’ risk of health care–associated infection (HAI). To gain understanding of this evidence base, a systematic review was conducted, and 42 articles were audited. The most common infection studied was bloodstream infection (n=18; 43%). The majority of researchers examined nurse staffing (n=38; 90%); of these, only 7 (18%) did not find a statistically significant association between nurse staffing variable(s) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 62 publications
7
63
0
7
Order By: Relevance
“…This study showed that higher nursing care hours was associated with fewer CLABSIs and shorter LOS, which is consistent with trends in previous studies [33]. Moreover, the results also suggest a nursestaffing benchmark to consider.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that higher nursing care hours was associated with fewer CLABSIs and shorter LOS, which is consistent with trends in previous studies [33]. Moreover, the results also suggest a nursestaffing benchmark to consider.…”
Section: Discussionsupporting
confidence: 91%
“…Staffing levels and composition in dialysis facilities are ultimately modifiable factors that can be optimized and thereby improve patient outcomes [38, 39]. Structural staffing issues, specifically inadequate nurse staffing in acute care hospitals, have been linked to heightened risk of infection [40], mortality [41], and other adverse consequences [42-45]. Adequacy of dialysis clinic staffing and quality of care are linked [46], although what constitutes “adequate” staffing at dialysis facilities has not yet been defined, particularly with respect to ameliorating hospitalization risk [47].…”
Section: Discussionmentioning
confidence: 99%
“…La razón entre camas de UCI y personal de enfermería, y el lavado de manos son factores independientes que tienen un alto impacto en la incidencia de infecciones asociadas al cuidado de la salud 18,19 . El estudio INICC y otros han mostrado la baja …”
Section: Discussionunclassified